Tumor-Targeted Gene Silencing IDO Synergizes PTT-Induced Apoptosis and Enhances Anti-tumor Immunity - Zhang, Yujuan; Feng, Yuanyuan; Huang, Yanqing; Wang, Yifan; Qiu, Li; Liu, Yanling; Peng, Shanshan; Li, Rong; Kuang, Nanzhen; Shi, Qiaofa; Shi, Yanmei; Chen, Yiguo; et al. (Frontiers in Immunology, 2020)
Background: Photothermal therapy (PTT) has been demonstrated as a promising cancer treatment approach, which can be modulated to induce apoptosis instead of necrosis via adjusting irradiation conditions. Recently, an abscopal anti-tumor immunity is highlighted, in which PTT on primary tumor also induced repression of distant tumors. For PTT treating cancers, the mechanism and the role of immunochenck points to enhance anti-tumor immunity is urgently needed to investigate. Methods: We prepared a multi-functional gold nanorod reagent, GMPF-siIDO, that is composed of gold nanorods (GNRs) acting as the nano-platform and photothermal sensitizer, folic acid (FA) as the tumor-targeting moiety, and IDO-specific RNA (siIDO) as an immune-stimulator functionality for inducing anti-tumor immunity. For this study, we adjust the irradiation condition of PTT to induce apoptosis and silence the immunocheck point indoleamine 2,3 dioxygeonase (IDO), silmutaneously. Results: Our studies firstly provide evidences that photothermal effects, killing the tumor cells mainly via inducing apoptosis, can significantly improve antitumor immunity only when IDO was down-regulated in TME through significant increases of localized CD8+ and CD4+ lymphocytes in tumor tissue, downregulation of CD8+ and CD4+ lymphocyte apoptosis, and upregulation of antitumor cytokines, TNF-α and IFN-γ. Conclusion: In this study, we for the first time validated the role of IDO as a negative regulator for both PTT-induced tumor cell apoptosis and anti-tumor immunity; IDO is critical immune checkpoint that impedes the PTT efficient while combination of gene knockdown of IDO in TME enhances anti-tumor efficacy of PTT.